Komunikasi Terapeutik dalam Penyembuhan Pengguna Narkoba di Rehabilitasi Kota Baubau - Saputra, Rizky Febry; Maulana, Harry Fajar; Hidayatullah, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of therapeutic communication in the rehabilitation process of drug users at the Class II A Baubau Correctional Facility (Lapas). Using a qualitative descriptive approach, data were collected through interviews with counselors and residents, as well as direct observation. The results show that therapeutic communication, based on empathy and attention, implemented through the Therapeutic Community (TC) model, is effective in building trust between counselors and residents, which in turn increases residents' motivation to actively engage in the rehabilitation process. Challenges faced include residents' difficulty in opening up at the beginning of rehabilitation, but with a non-coercive approach and the family-like atmosphere applied within TC, counselors succeeded in supporting positive changes in the residents' lives. This study also highlights the importance of further training for counselors to optimize therapeutic communication in drug rehabilitation